2023
DOI: 10.3389/ti.2023.10936
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic Ex Vivo Machine Perfusion of Discarded Human Pancreas Allografts: A Feasibility Study

Abstract: Pancreas transplantation is the only curative treatment for patients with complicated diabetes, and organ shortage is a common and increasing problem. Strategies to expand the donor pool are needed, and normothermic ex vivo perfusion of the pancreas has the potential to test and repair grafts before implantation. Between January 2021 and April 2022, six human pancreases, declined for transplantation or islet isolation, were perfused using a previously established method by our group. All 6 cases were successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The pancreas is particularly susceptible to edema and ischemic damage during retrieval and preservation, which can lead to microcirculatory dysfunction, likely a major reason why pancreatic perfusion has not attracted as much attention as it has for other organs previously [69][70][71]. Nevertheless, recent experimental and initial human trials of pancreatic machine perfusion look promising [69,[72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…The pancreas is particularly susceptible to edema and ischemic damage during retrieval and preservation, which can lead to microcirculatory dysfunction, likely a major reason why pancreatic perfusion has not attracted as much attention as it has for other organs previously [69][70][71]. Nevertheless, recent experimental and initial human trials of pancreatic machine perfusion look promising [69,[72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they noted that pancreases from DCD donors displayed the lowest basal and glucose-stimulated insulin levels, with mean insulin levels significantly below those observed in DBD pancreases. Similarly, a Canadian research group observed an increase in insulin levels in the perfusate of only DBD pancreases during ex vivo normothermic perfusion in experimental settings ( 27 ). Importantly, both studies had limited sample sizes ( 25 , 26 ), underscoring the need for future investigations with larger cohorts to thoroughly explore variations in outcomes between DCD and DBD pancreases.…”
Section: Introductionmentioning
confidence: 92%
“…As such, Parmentier et al performed a feasibility study on cases performed between January 2021 and April 2022 in which 6 grafts that were declined for transplantation or islet isolation were placed on a normothermic ex vivo perfusion pump. 40 All 6 grafts were perfused without issue for 4 hours. They remained metabolically active, and biopsies showed minimal tissue injury, suggesting that the use of normothermic machine perfusion is feasible in pancreas transplantation.…”
Section: Donor Managementmentioning
confidence: 99%